1986
DOI: 10.2172/6685301
|View full text |Cite
|
Sign up to set email alerts
|

Fuels from microalgae: Technology status, potential, and research requirements

Abstract: Price: Microfiche A01 Printed Copy A08 Codes are used for pricing all publications. The code is determined by the number of pages In the publtcatlon. Information pertaining to the pricing codes can be found in the current tssue of t h e lollow~ng pliblfcilt~ofls, which are generally available in most libraries: Energy Research Abstracts,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…The two best ways to decrease cost are to enhance the lipid concentration within algae cells and to accelerate the accumulation of algae biomass. After detailed and careful research and analyses, Neenan et al (1986) concluded that only if the lipid concentration achieved 50-60% of algae dry biomass would algal biodiesel be competitive compared with fossil energy. Therefore, increasing lipid production is an efficient method for lowering the cost and accelerating the process of commercial algae biodiesel production.…”
Section: Discussionmentioning
confidence: 99%
“…The two best ways to decrease cost are to enhance the lipid concentration within algae cells and to accelerate the accumulation of algae biomass. After detailed and careful research and analyses, Neenan et al (1986) concluded that only if the lipid concentration achieved 50-60% of algae dry biomass would algal biodiesel be competitive compared with fossil energy. Therefore, increasing lipid production is an efficient method for lowering the cost and accelerating the process of commercial algae biodiesel production.…”
Section: Discussionmentioning
confidence: 99%
“…For microalgal lipids to be cost competitive as a biofuel source, a feedstock organism should contain high lipid contents (21). Our results demonstrated that the lipid content of C. zofingiensis was evidently higher than those of some other Chlorella strains, such as, Chlorella minutissima (57%) (4), Chlorella emersonii (63%) (4), Chlorella vulgaris (58%) (22), C. vulgaris (56.6%) (23), Chlorella protothecoidesa (57.8%) (5).…”
Section: Discussionmentioning
confidence: 99%
“…The Neenan et al (1986) report, which emphasized the algal biomass to fuel conversion processes, also specified a soybean process, without discussion of its applicability. They called for evaluation of alternative solvents, but that approach is not credible, as from laboratory experiments the solvent to biomass ratios required are very high, for any solvent tested (and all likely ones have been), and the extraction conditions, required to recover lipids from microalgae would be difficult to scale-up (Benemann, et al, 1984).…”
Section: Harvesting and Processingmentioning
confidence: 99%
“…Thus, in this most critical area, no credible technical approach has been developed previously. In this regards, it Neenan et al (1986) study used a fixed composition biomass (30% lipid, 20% carbohydrate, 32% protein) for all the conversion processes, a composition neither optimal for lipid production nor realistic for ethanol recovery, the two major products of interest. Also, the actual costs for processing lipid triglycerides to higher value fuels (e.g.…”
Section: Harvesting and Processingmentioning
confidence: 99%
See 1 more Smart Citation